Quantum fluorescence oil displacement agent and preparation method thereof
Patent Information
- Application Number
- CN202610861998.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-15
- Publication Date
- 2026-10-13
AI Technical Summary
[0008]针对现有碳量子点驱油剂存在的掺杂可控性差、表面活性剂结合力弱、高温高盐环境下荧光稳定性不足、驱油效率低的技术问题,本发明提供一种兼具强荧光示踪功能和优异驱油性能的量子荧光驱油剂及其制备方法
(1)本发明提供的量子荧光驱油剂为表面共价接枝有季铵盐型和甜菜碱型两性表面活性剂的氨基改性碳量子点材料,其碳量子点内部为N、S、P三元杂原子共掺杂结构。该结构设计使得驱油剂兼具超小尺寸、优异的分散性和丰富的表面活性位点,能够有效避免颗粒团聚堵塞地层孔隙,满足低渗透、致密油藏的现场注入与深部驱油应用要求。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of petrochemical technology, specifically relating to a quantum fluorescent oil displacement agent and its preparation method. Background Technology
[0002] As oilfield development deepens, reservoir conditions become increasingly complex. Conventional oil displacement technologies, such as conventional waterflooding and polymer flooding, are struggling to meet the demands for efficient development in the face of increased reservoir heterogeneity, highly dispersed residual oil distribution, and reduced formation permeability. During waterflooding, fingering is prone to occur due to differences in oil-water viscosity and reservoir heterogeneity, leading to low oil displacement efficiency. While polymer flooding can improve efficiency to some extent, issues such as polymer adsorption and retention in the formation, and shear degradation limit its further application. Therefore, developing new, highly efficient oil displacement technologies has become an urgent technical problem to be solved in the oilfield development field.
[0003] Nanomaterials, with their unique physicochemical properties, have shown great application potential in many fields, and their application in oilfield development has received increasing attention in recent years. The small size effect, high specific surface area, and special surface properties of nanomaterials enable them to interact more strongly with crude oil and formation rocks during oil displacement, thereby improving oil displacement efficiency. Among them, carbon quantum dots, as a novel nanomaterial, have become an important research direction for oil displacement agents due to their unique fluorescence properties, showing great potential as oil displacement agents in oilfield extraction. However, existing carbon quantum dot-based oil displacement agents still face the following technical challenges in practical applications:
[0004] Poor controllability of doping limits the functional enhancement effect. Existing fluorescent tracer-type carbon quantum dot oil displacement agents mostly use single nitrogen element doping, such as urea as nitrogen source. The combination form of nitrogen element is random, and the proportion of effective active nitrogen sites is low. As a result, the effect of nitrogen doping on improving the performance of carbon quantum dots is limited. It cannot give full play to the role of heteroatom doping in enhancing interfacial adsorption and salt resistance. The adaptability of oil displacement agents in complex reservoir environments is insufficient.
[0005] Surfactants exhibit weak binding affinity and poor long-term stability. In the preparation of oil displacement agents, surfactants are typically introduced to improve the surface properties and dispersibility of carbon quantum dots. However, in existing technologies, surfactants are mostly bound to carbon quantum dots through physical composite mechanisms, lacking stable covalent bonds. This binding method leads to the surfactant's easy detachment under conditions of high formation salinity and high shear, resulting in poor long-term stability of the oil displacement agent, significant interfacial tension rebound, and difficulty in maintaining a stable oil displacement state.
[0006] Insufficient fluorescence stability and low tracer accuracy are problems. Oil reservoir environments are typically characterized by high temperature, high salinity, and high hardness, placing stringent requirements on the fluorescence stability and temperature and salt resistance of displacement agents. Existing carbon quantum dot displacement agents exhibit poor tracer stability due to the susceptibility of fluorescence intensity to salinity and temperature. In high-temperature and high-salinity environments, the displacement agent is prone to aggregation and precipitation, resulting in a short effective period that cannot meet the needs of long-term oilfield production. This also leads to decreased tracer accuracy, making it difficult to accurately monitor the oil displacement process.
[0007] The aforementioned problems result in shortcomings in existing carbon quantum dot oil displacement agents, such as poor long-term oil displacement performance and limited adaptability to complex reservoirs, failing to fully leverage the dual advantages of carbon quantum dots in oil displacement and enhanced oil recovery, as well as fluorescence tracing. Therefore, developing a carbon quantum dot oil displacement agent that combines strong fluorescence tracing capabilities with excellent oil displacement performance not only promises to solve problems in existing technologies such as unstable surface functional groups, poor doping controllability, weak surfactant binding, uneven product particle size distribution, and insufficient fluorescence stability, temperature and salt resistance, but also enables real-time and precise monitoring of the oil displacement process through fluorescence tracing. Summary of the Invention
[0008] To address the technical problems of existing carbon quantum dot oil displacement agents, such as poor doping controllability, weak surfactant binding force, insufficient fluorescence stability under high temperature and high salt conditions, and low oil displacement efficiency, this invention provides a quantum fluorescent oil displacement agent with both strong fluorescence tracing function and excellent oil displacement performance, as well as its preparation method.
[0009] On one hand, the present invention provides a method for preparing a quantum fluorescent oil displacement agent, the method comprising the following steps: S1. Humic acid, phytic acid, urea and thiourea are dissolved in deionized water and hydrothermally reacted at 170~180℃ for 4~6h. Carbon quantum dot particles are obtained after post-treatment. S2. The carbon quantum dot particles obtained in S1 are dispersed in anhydrous ethanol and condensed with hydrolyzed and activated γ-aminopropyltriethoxysilane at pH 4-5 and 58-60℃ for 4-6 hours under the catalysis of dibutyltin dilaurate to obtain amino-modified carbon quantum dot materials. S3. The amino-modified carbon quantum dot material obtained in S2 is grafted with hexadecyltrimethylammonium bromide and betaine at pH 8-9 and 55-60℃ for 6-8 hours to obtain the quantum fluorescent oil displacement agent.
[0010] As a preferred technical solution, the mass ratio of humic acid, phytic acid, urea and thiourea in step S1 is 1.5~2.5:0.1~0.5:0.7~1.0:0.05~0.15.
[0011] As a preferred technical solution, the post-processing in step S1 includes: sequentially filtering with filter membranes with pore sizes of 0.8 μm and 0.45 μm.
[0012] As a preferred technical solution, the post-processing further includes: dialysis followed by freeze-drying using a combination of dialysis bags with molecular weight cutoffs of 4000 Da and 3000 Da.
[0013] As a preferred technical solution, the temperature of the hydrothermal reaction in step S1 is 180°C and the reaction time is 4 hours.
[0014] As a preferred technical solution, the condensation reaction in step S2 is carried out at a temperature of 60°C, a pH of 4.5, and a reaction time of 4 hours; the grafting reaction in step S3 is carried out at a temperature of 58°C, a pH of 8.5, and a reaction time of 6.5 hours.
[0015] As a preferred technical solution, the mass ratio of humic acid, phytic acid, urea, and thiourea is 2.5:0.2:1.0:0.15.
[0016] In another aspect, a quantum fluorescent oil-repellent agent prepared by the preparation method described in this invention is also provided.
[0017] Those skilled in the art will understand that, through a hydrothermal reaction at 170-180℃, nitrogen, sulfur, and phosphorus elements in the raw materials can be covalently incorporated into the carbon framework of carbon quantum dots, forming a stable N, S, and P ternary co-doped structure. This achieves cross-linking enhancement from within the carbon framework, improving the structural stability and fluorescence properties of the quantum dots. Simultaneously, in a weakly alkaline environment of pH 8-9, the active amino groups on the surface of amino-modified carbon quantum dots can covalently bond with hexadecyltrimethylammonium bromide and betaine molecules, allowing these two surfactants to be firmly grafted onto the carbon quantum dot surface via chemical bonds. Unlike traditional simple physical adsorption and electrostatic recombination, this covalent grafting modification mode exhibits stronger binding force and higher system stability, effectively ensuring the comprehensive application performance of the oil displacement agent in complex reservoir environments.
[0018] Finally, the present invention also provides the application of the quantum fluorescent oil displacement agent in oilfield development. Specifically, the quantum fluorescent oil displacement agent is injected into the oil reservoir formation to improve the crude oil recovery rate, and the oil displacement process is monitored in real time by detecting its fluorescence signal.
[0019] As a preferred technical solution, the quantum fluorescent oil displacement agent is injected into the formation at a concentration of 0.3wt%~0.5wt%; the oil reservoir is a high-temperature and high-salinity oil reservoir with a temperature of 80~120℃ and a salinity of 20000~50000mg / L; and the detection wavelength of the fluorescent signal is 500~600nm.
[0020] Compared with the prior art, the technical solution provided by the present invention has at least the following beneficial effects or advantages: (1) The quantum fluorescent oil displacement agent provided by the present invention is an amino-modified carbon quantum dot material with quaternary ammonium salt and betaine-type amphoteric surfactants covalently grafted onto its surface. The carbon quantum dots have a N, S, P ternary heteroatom co-doped structure. This structural design enables the oil displacement agent to have ultra-small size, excellent dispersibility and abundant surface active sites, which can effectively avoid particle agglomeration and blockage of formation pores, and meet the requirements of in-situ injection and deep oil displacement applications in low-permeability and tight oil reservoirs.
[0021] (2) This invention achieves cross-linking enhancement from within the carbon framework through N, S, and P ternary heteroatom co-doping. Simultaneously, a dense Si-OC protective layer is formed on the quantum dot surface through covalent grafting mediated by γ-aminopropyltriethoxysilane as a silane coupling agent, forming a dual stabilization mechanism of "internal enhancement + external protection". Experimental results show that the quantum fluorescent oil displacement agent prepared in this invention, after aging for 7 days under high temperature and high salt (mineralization 35000 mg / L) conditions at 80℃, 100℃, and 120℃, retains fluorescence rates of over 94%, over 88%, and over 77%, respectively, which are far superior to the comparative samples doped with a single N or lacking any dopant element, demonstrating excellent high temperature and high salt fluorescence stability.
[0022] (3) In this invention, amino active functional groups are introduced onto the surface of carbon quantum dots using a silane coupling agent, and then hexadecyltrimethylammonium bromide (CTAB) and betaine are covalently grafted onto the surface of the carbon quantum dots to form a stable covalent bond structure. This design enables the oil displacement agent to be efficiently adsorbed and orderly arranged at the oil-water interface, reducing the oil-water interfacial tension to a low level of 0.001 mN / m (kerosene) and 0.108~0.169 mN / m (extended crude oil), which is far superior to the comparative samples prepared by physical composite methods. Core displacement test results show that the oil displacement efficiency of the quantum fluorescent oil displacement agent prepared in this invention is as high as 19.3%~25.6%, which is significantly improved compared with the prior art.
[0023] (4) In this invention, the surfactant is grafted onto the surface of carbon quantum dots through covalent bonds. The combination is strong and it is not easy to fall off under the conditions of high mineralization and high shear in the formation. It can maintain a long-term stable low interfacial tension state and ensure a continuous and efficient oil displacement effect.
[0024] (5) The quantum fluorescent oil displacement agent provided by this invention has stable fluorescence emission characteristics in the wavelength range of 500~600nm. After injection into the formation, the breakthrough time and migration distribution of the oil displacement agent can be determined in real time by detecting the change in the peak fluorescence intensity in the produced fluid of the production well, providing visualized data support for oilfield development and realizing the integrated application of oil displacement and tracing. Detailed Implementation
[0025] The technical solution of the present invention will be described below with reference to the embodiments. However, the present invention is not limited to the following embodiments.
[0026] To enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described below with reference to specific embodiments, but the embodiments are not intended to limit the present invention.
[0027] Unless otherwise specified, the test methods and detection methods described in the following embodiments are conventional methods; unless otherwise specified, the reagents and materials are commercially available.
[0028] Example 1 This example demonstrates the preparation of a quantum fluorescent oil displacement agent.
[0029] S1. Dissolve 2g of humic acid, 0.1g of phytic acid, 0.9g of urea, and 0.1g of thiourea in 40g of deionized water, and then ultrasonically disperse for 20min (ultrasonic power 220W). Transfer the mixed solution to a reactor and react at 170℃ for 5h, then cool to room temperature.
[0030] S2. Dissolve the product obtained in S1 in 55g of deionized water, sonicate for 6min, filter once with a filter membrane with a pore size of 0.8μm, filter twice with a filter membrane with a pore size of 0.45μm to remove larger particles, and dialyze with a combination of dialysis bags with a molecular weight cutoff of 4000Da and 3000Da to remove small molecule impurities to obtain a carbon quantum dot solution, and then freeze-dry to prepare carbon quantum dot particles.
[0031] S3. Weigh 1g of the carbon quantum dot particles obtained in S2, add 55g of anhydrous ethanol, and prepare a dispersion. Disperse the particles using ultrasonication at 220W and 40kHz for 25min to ensure uniform dispersion of the carbon quantum dots in the system. Centrifuge the dispersed mixture at 7000rpm for 12min to remove any large, undispersed agglomerates. Collect the supernatant as the carbon quantum dot supernatant for later use.
[0032] γ-aminopropyltriethoxysilane was measured and mixed with deionized water at a volume ratio of 1:5. A small amount of glacial acetic acid was added to adjust the pH of the system to 4-5. The mixture was stirred continuously at room temperature for 30 minutes to allow γ-aminopropyltriethoxysilane to be fully hydrolyzed to generate silanol active groups.
[0033] The hydrolyzed and activated γ-aminopropyltriethoxysilane solution was slowly added dropwise to the carbon quantum dot supernatant at a volume ratio of 1:10. Simultaneously, 0.1% (w / w) of dibutyltin dilaurate (DBTDL) was added as a condensation catalyst. The system was heated to 58°C and stirred at this temperature for 4.5 h. Throughout the reaction, the pH was maintained at 4-5 using glacial acetic acid to suppress the self-condensation side reaction of the silanol groups. After the reaction, the mixture was allowed to cool naturally to room temperature, and then diluted with excess anhydrous ethanol at a volume ratio of 1:3 to terminate the condensation reaction. The mixture was centrifuged at 12000 rpm for 20 min, and the bottom solid precipitate was collected. The modified product was washed three times with anhydrous ethanol to completely remove unreacted γ-aminopropyltriethoxysilane monomers and small molecule byproducts, yielding amino-modified carbon quantum dot materials.
[0034] S4. Dissolve 1.2g of the amino-modified carbon quantum dot material obtained in S3 in 50g of anhydrous ethanol, add 1.5g of hexadecyltrimethylammonium bromide and 0.2g of betaine, and adjust the pH of the system with ammonia water throughout the process to maintain stability at 8-9. Under nitrogen protection, the temperature is controlled at 60℃, and the reaction time is 6h. After the reaction is completed, the anhydrous ethanol is removed using a rotary evaporator to obtain the quantum fluorescent oil displacement agent, labeled as No. 1 quantum fluorescent oil displacement agent.
[0035] Example 2 This example demonstrates the preparation of a quantum fluorescent oil displacement agent.
[0036] S1. Dissolve 2.5g of humic acid, 0.2g of phytic acid, 1.0g of urea, and 0.15g of thiourea in 50g of deionized water, and then ultrasonically disperse for 25min (ultrasonic power 200W). Transfer the mixed solution to a reactor and react at 180℃ for 4h, then cool to room temperature.
[0037] S2. Dissolve the product obtained in S1 in 60g of deionized water, sonicate for 6min, filter once with a filter membrane with a pore size of 0.8μm, filter twice with a filter membrane with a pore size of 0.45μm to remove larger particles, and dialyze with a combination of dialysis bags with a molecular weight cutoff of 4000Da and 3000Da to remove small molecule impurities to obtain a carbon quantum dot solution, and then freeze-dry to prepare carbon quantum dot particles.
[0038] S3. Weigh 1g of the carbon quantum dot particles obtained in S2, add 50g of anhydrous ethanol, and prepare a dispersion. Disperse the particles using ultrasonication at 200W and 40kHz for 30min to ensure uniform dispersion of the carbon quantum dots in the system. Centrifuge the dispersed mixture at 8000rpm for 10min to remove any large, undispersed agglomerates. Collect the supernatant as the carbon quantum dot supernatant for later use.
[0039] γ-aminopropyltriethoxysilane was measured and mixed with deionized water at a volume ratio of 1:5. A small amount of glacial acetic acid was added to adjust the pH of the system to 4-5. The mixture was stirred continuously at room temperature for 30 minutes to allow γ-aminopropyltriethoxysilane to be fully hydrolyzed to generate silanol active groups.
[0040] The hydrolyzed and activated γ-aminopropyltriethoxysilane solution was slowly added dropwise to the carbon quantum dot supernatant at a volume ratio of 1:12. Simultaneously, 0.2% (w / w) of dibutyltin dilaurate (DBTDL) was added as a condensation catalyst. The system was heated to 60°C and stirred at this temperature for 4 hours. Throughout the reaction, the pH was maintained at 4-5 using glacial acetic acid to suppress the self-condensation side reaction of the silanol groups. After the reaction, the mixture was allowed to cool naturally to room temperature, and then diluted with excess anhydrous ethanol at a volume ratio of 1:3 to terminate the condensation reaction. The mixture was centrifuged at 12000 rpm for 20 minutes, and the bottom solid precipitate was collected. The modified product was washed three times with anhydrous ethanol to completely remove unreacted γ-aminopropyltriethoxysilane monomers and small molecule byproducts, yielding amino-modified carbon quantum dot materials.
[0041] S4. Dissolve 1.2g of the amino-modified carbon quantum dot material obtained in S3 in 60g of anhydrous ethanol, add 1.4g of hexadecyltrimethylammonium bromide and 0.25g of betaine, and adjust the pH of the system with ammonia water throughout the process to maintain stability at 8-9. Under nitrogen protection, the temperature is controlled at 58℃, and the reaction time is 6.5h. After the reaction, remove the anhydrous ethanol using a rotary evaporator to obtain the quantum fluorescent oil displacement agent, labeled as #2 quantum fluorescent oil displacement agent. The fluorescence wavelength range of #2 quantum fluorescent oil displacement agent is detected to be 500-600nm. Applying #2 quantum fluorescent oil displacement agent at a concentration of 0.5wt% to a core displacement test, the breakthrough time (the point of sudden increase in fluorescence intensity) and subsequent migration and distribution trend of the oil displacement agent can be clearly identified by detecting the fluorescence intensity change curve of the produced fluid at 550nm.
[0042] Example 3 This example demonstrates the preparation of a quantum fluorescent oil displacement agent.
[0043] S1. Dissolve 1.5g of humic acid, 0.5g of phytic acid, 0.7g of urea, and 0.05g of thiourea in 50g of deionized water, and then ultrasonically disperse for 30min (ultrasonic power 200W). Transfer the mixed solution to a reactor and react at 170℃ for 6h, then cool to room temperature.
[0044] S2. Dissolve the product obtained in S1 in 60g of deionized water, sonicate for 6min, filter once with a filter membrane with a pore size of 0.8μm, filter twice with a filter membrane with a pore size of 0.45μm to remove larger particles, and dialyze with a combination of dialysis bags with a molecular weight cutoff of 4000Da and 3000Da to remove small molecule impurities to obtain a carbon quantum dot solution, and then freeze-dry to prepare carbon quantum dot particles.
[0045] S3. Weigh 1g of the carbon quantum dot particles obtained in S2, add 65g of anhydrous ethanol, and prepare a dispersion. Disperse the particles using ultrasonication at 200W and 40kHz for 35min to ensure uniform dispersion of the carbon quantum dots in the system. Centrifuge the dispersed mixture at 9000rpm for 8min to remove any large, undispersed agglomerates. Collect the supernatant as the carbon quantum dot supernatant for later use.
[0046] γ-aminopropyltriethoxysilane was measured and mixed with deionized water at a volume ratio of 1:5. A small amount of glacial acetic acid was added to adjust the pH of the system to 4-5. The mixture was stirred continuously at room temperature for 30 minutes to allow γ-aminopropyltriethoxysilane to be fully hydrolyzed to generate silanol active groups.
[0047] The hydrolyzed and activated γ-aminopropyltriethoxysilane solution was slowly added dropwise to the carbon quantum dot supernatant at a volume ratio of 1:11. Simultaneously, 0.2% (w / w) of dibutyltin dilaurate (DBTDL) was added as a condensation catalyst. The system was heated to 60°C and stirred at this temperature for 5 hours. Throughout the reaction, the pH was maintained at 4-5 using glacial acetic acid to suppress the self-condensation side reaction of the silanol groups. After the reaction, the mixture was allowed to cool naturally to room temperature, and then diluted with excess anhydrous ethanol at a volume ratio of 1:3 to terminate the condensation reaction. The mixture was centrifuged at 12000 rpm for 20 minutes, and the bottom solid precipitate was collected. The modified product was washed three times with anhydrous ethanol to completely remove unreacted γ-aminopropyltriethoxysilane monomers and small molecule byproducts, yielding amino-modified carbon quantum dot materials.
[0048] S4. Dissolve 1.5g of the amino-modified carbon quantum dot material obtained in S3 in 60g of anhydrous ethanol, add 1.7g of hexadecyltrimethylammonium bromide and 0.3g of betaine, and adjust the pH of the system with ammonia water throughout the process to maintain a stable pH of 8-9. Under nitrogen protection, the temperature is controlled at 55℃, and the reaction time is 8h. After the reaction is completed, the anhydrous ethanol is removed using a rotary evaporator to obtain the quantum fluorescent oil displacement agent.
[0049] Comparative Example 1 This comparative example uses a publicly disclosed method in the prior art to prepare a quantum fluorescent oil displacement agent.
[0050] S1. Dissolve 2g of humic acid and 1.1g of urea in 30g of deionized water and then sonicate for 40min. Place the mixed solution in a microwave reactor and react for 8min, then cool to room temperature.
[0051] S2. Dissolve the product obtained in S1 in 80g of deionized water, sonicate for 8min, remove larger particles using a filter membrane with a pore size of 0.45μm, remove small molecule impurities using a dialysis bag with a molecular weight cutoff of 3500Da to obtain a carbon quantum dot solution, and then freeze-dry to prepare carbon quantum dot particles.
[0052] S3. Dissolve 1g of carbon quantum dot particles obtained in S2 in 60g of anhydrous ethanol, then add 2.4g of hexadecyltrimethylammonium bromide. Under nitrogen protection, add 1.2g of triethylamine to promote the reaction. The temperature is controlled at 80℃, and the reaction time is 6h. After the reaction is complete, remove the anhydrous ethanol using a rotary evaporator. The resulting quantum fluorescent oil displacement agent is labeled as #1 contrast agent.
[0053] Comparative Example 2 The only difference between this comparative example and Example 2 is that phytic acid is not added in step S1. Specifically, S1 involves dissolving 2.5 g of humic acid, 1.0 g of urea, and 0.15 g of thiourea in 50 g of deionized water, followed by ultrasonic dispersion for 25 min (ultrasonic power 200 W). The mixed solution is then transferred to a reactor and reacted at 180°C for 4 h, followed by cooling to room temperature. The remaining steps are the same as in Example 2. The resulting quantum fluorescent oil-repellent agent is labeled as #2 contrast agent.
[0054] Comparative Example 3 The only difference between this comparative example and Example 2 is that thiourea is not added in step S1. Specifically, S1 involves dissolving 2.5 g of humic acid, 0.2 g of phytic acid, and 1.0 g of urea in 50 g of deionized water, followed by ultrasonic dispersion for 25 min (ultrasonic power 200 W). The mixed solution is then transferred to a reactor and reacted at 180°C for 4 h, followed by cooling to room temperature. The remaining steps are the same as in Example 2. The resulting quantum fluorescent oil-repellent agent is labeled as #3 contrast agent.
[0055] Comparative Example 4 The difference between this comparative example and Example 2 is that the γ-aminopropyltriethoxysilane modification step is omitted.
[0056] S1. Dissolve 2.5g of humic acid, 0.2g of phytic acid, 1.0g of urea, and 0.15g of thiourea in 50g of deionized water, and then ultrasonically disperse for 25min (ultrasonic power 200W). Transfer the mixed solution to a reactor and react at 180℃ for 4h, then cool to room temperature.
[0057] S2. Dissolve the product obtained in S1 in 60g of deionized water, sonicate for 6min, filter once with a filter membrane with a pore size of 0.8μm, filter twice with a filter membrane with a pore size of 0.45μm to remove larger particles, and dialyze with a combination of dialysis bags with a molecular weight cutoff of 4000Da and 3000Da to remove small molecule impurities to obtain a carbon quantum dot solution, and then freeze-dry to prepare carbon quantum dot particles.
[0058] S3. Dissolve 1.2g of the carbon quantum dot particles obtained in S2 in 60g of anhydrous ethanol, add 1.4g of hexadecyltrimethylammonium bromide and 0.25g of betaine, and adjust the pH of the system with ammonia water throughout the process to maintain a stable pH of 8-9. Under nitrogen protection, the temperature is controlled at 58℃, and the reaction time is 6.5h. After the reaction is complete, remove the anhydrous ethanol using a rotary evaporator to obtain the quantum fluorescent oil displacement agent. Labeled as #4 contrast agent.
[0059] Comparative Example 5 The difference between this comparative example and Example 2 is that only hexadecyltrimethylammonium bromide was used in step S4, and betaine was not used.
[0060] Step S4 is as follows: 1.2g of the amino-modified carbon quantum dot material obtained in S3 is dissolved in 60g of anhydrous ethanol, and 1.65g of hexadecyltrimethylammonium bromide is added. The pH of the system is maintained at 8-9 throughout the process using ammonia. Under nitrogen protection, the temperature is controlled at 58℃, and the reaction time is 6.5h. After the reaction, the anhydrous ethanol is removed using a rotary evaporator to obtain the quantum fluorescent oil displacement agent, labeled as #5 contrast agent.
[0061] Example 4 This embodiment tests the performance of different quantum fluorescent oil displacement agents using samples.
[0062] 4.1 Particle size measurement The particle size distribution of the quantum fluorescent oil repellents (No. 1 to No. 3) prepared in Examples 1 to 3 was measured using a Malvern Zetasizer Nano ZS90 nanoparticle size analyzer. Each sample was dispersed in deionized water at a final concentration of 0.3 wt%, and each treatment was measured three times. The test results are shown in Table 1.
[0063] Table 1. Statistical results of average particle size of different quantum fluorescent oil displacement agents
[0064] Note: PDI < 0.2 As shown in Table 1, the quantum fluorescent oil displacement agent prepared by this invention has the advantages of uniform particle size, excellent dispersibility and controllable nanoscale size. It can effectively avoid particle agglomeration and blockage of formation pores, and can meet the requirements of in-situ injection and deep oil displacement applications in low-permeability and tight oil reservoirs. It provides a good structural basis for improving the fluorescent tracing and oil displacement effects.
[0065] 4.2 Fluorescence performance test Quantum fluorescent oil displacement agents #1-3 and contrast agents #1-5 were dispersed at a concentration of 0.5 wt% in simulated saline solution (NaCl / CaCl2 / MgCl2 mass ratio 7:1:1) with a salinity of 35000 mg / L, and aged for 7 days at constant temperatures of 80℃, 100℃, and 120℃, respectively. The fluorescence emission spectra of the solutions before and after aging were detected using a fluorescence spectrophotometer. The fluorescence retention values of different quantum fluorescent oil displacement agents were statistically analyzed, and the stability of different quantum fluorescent oil displacement agents was tested. The results are shown in Table 2.
[0066] Table 2. Stability test results of different quantum fluorescent oil displacement agents at different temperatures.
[0067] As shown in Table 2, after aging at 80℃, 100℃, and 120℃ for 7 days, the fluorescence retention rates of quantum fluorescent oil displacement agents 1#~3# reached over 94%, over 88%, and over 77%, respectively. Even under the most stringent conditions of 120℃ and 35000mg / L mineralization, they still maintained excellent fluorescence performance. The fluorescence retention rates of contrast agents 1#~5# at different temperatures were significantly lower than those of the quantum fluorescent oil displacement agents 1#~3# provided in this invention. In particular, at 120℃, the retention rate of the contrast agent 1# was only 58.1%, nearly 20 percentage points lower than the lowest 77.1% of this invention. This indicates that the oil displacement agent has excellent fluorescence stability under high temperature and high salt conditions. The quantum fluorescent oil displacement agent prepared in this invention has excellent high temperature and high salt fluorescence stability. This is due to its unique NSP ternary heteroatom co-doped carbon quantum dot structure, which achieves cross-linking enhancement from the inside of the carbon skeleton, effectively inhibiting the thermal degradation and shedding of heteroatom functional groups. In addition, silane modification further increases fluorescence stability. The fluorescence stability of contrast agent #4 (silane-deficient modification) decreased significantly, proving that the dual mechanism of "internal enhancement and external protection" formed by NSP co-doping and silane-amino surface modification is the core technical means to ensure fluorescence stability.
[0068] 4.3 Interface Activity Test Quantum fluorescent oil displacement agents 1-3 and contrast agents 1-5 were prepared into solutions with a concentration of 0.3 wt% using deionized water. The interfacial tension of the sample solutions to kerosene and extended crude oil was tested using an interfacial tension meter at 25°C. The interfacial tension data were read after 30 minutes of testing. The test results are shown in Table 3.
[0069] Table 3. Results of interfacial activity tests for different quantum fluorescent oil displacement agents
[0070] As shown in Table 3, the interfacial tension of quantum fluorescent oil displacement agents 1# to 3# with kerosene reaches an ultra-low level of 0.001 mN / m; the interfacial tension with extended crude oil is also below 0.17 mN / m, with quantum fluorescent oil displacement agent 2# reaching as low as 0.108 mN / m. The interfacial tension of contrast agents 1# to 5# with kerosene (0.002~0.004 mN / m) and with extended crude oil (0.497~0.688 mN / m) is significantly higher than that of quantum fluorescent oil displacement agents 1# to 3# provided in this invention, differing by 1 to 2 orders of magnitude.
[0071] Comparative Example 5, without betaine, exhibited the worst interfacial activity, indicating that the introduction of betaine plays a crucial role in further reducing interfacial tension, particularly for complex crude oils (extended-stretch crude oils). Comparative agents 2-4 all showed increased interfacial tension due to the absence of phytic acid, thiourea, silane coupling agents, or betaine. This suggests that the co-doping of carbon quantum dots with NSP, the covalent grafting of γ-aminopropyltriethoxysilane, and the combined grafting of CTAB and betaine have a synergistic effect, collectively endowing the quantum fluorescent oil displacement agent with excellent adsorption and alignment capabilities at the oil-water interface.
[0072] The quantum fluorescent oil displacement agents #1 to #3 prepared in this invention possess extremely strong interfacial activity. They can reduce the oil-water interfacial tension to an ultra-low level (10). -3 (on the order of mN / m), indicating that the No. 1 to No. 3 quantum fluorescent oil displacement agents provided by this invention can efficiently strip crude oil from the rock surface and significantly improve oil washing efficiency.
[0073] 4.4 Evaluation of Displacement Effect The displacement effect was evaluated using 0.3 wt% of quantum fluorescent oil displacement agent 1-3 and 0.3 wt% of contrast agent 1-5. The displacement test was conducted in accordance with the "Method for Determination of Relative Permeability of Two-Phase Fluids in Rocks". The displacement effect of the oil displacement agent was characterized by the increase in oil displacement efficiency. The test results are shown in Table 4.
[0074] Table 4. Test results of oil displacement effect of different quantum fluorescent oil displacement agents
[0075] The displacement test results show that, under the same test conditions, the increase in oil displacement and oil displacement efficiency of the 1-3# quantum fluorescent oil displacement agents is much better than that of the 1# contrast agent, with the oil displacement efficiency improvement reaching up to 25.6%. With the optimization of the formulation system, the oil displacement performance gradually improves, and the 3# quantum fluorescent oil displacement agent has the best oil displacement effect.
[0076] The increase in oil displacement and efficiency of quantum fluorescent oil displacement agents 1-3 is far superior to that of contrast agents 2-4. The oil displacement effect of the contrast samples lacking a single component is significantly reduced. Phytic acid, thiourea heteroatom co-doping, γ-aminopropyltriethoxysilane amphiphilic modification, and CTAB and betaine compounding are necessary conditions for the high performance of quantum fluorescent oil displacement agents. The synergistic effect of each functional component gives the quantum fluorescent oil displacement agent excellent interfacial activity, wettability regulation and residual oil mobility, which is the core of its significant improvement in oil displacement efficiency.
[0077] Based on NSP co-doped carbon quantum dots, silane coupling agents were selected to perform surface grafting modification on the materials, and amino active functional groups were introduced. By constructing a stable Si-OC covalent bond structure, a dense protective layer was formed on the surface of the quantum dots, effectively inhibiting the thermal degradation and shedding of heteroatom functional groups under high temperature conditions. At the same time, the types of surface polar functional groups were enriched, enhancing the oil-water interface adsorption capacity, heavy oil dispersion and viscosity reduction performance, and rock wettability regulation effect, further improving the temperature and salt resistance and fluorescence tracer stability of the oil displacement agent.
[0078] NSP ternary co-doping enhances cross-linking from within the carbon framework, improving matrix structural stability; silane-amino surface modification constructs a protective interface from the outside. This dual action synergistically overcomes the shortcomings of insufficient thermal stability in single sulfide-based doped materials, endowing the composite oil displacement agent with excellent high-temperature compatibility, heavy oil viscosity reduction ability, and long-lasting fluorescent tracer performance. The quantum fluorescent oil displacement agent provided by this invention has significant advantages in multi-mechanism synergistic oil displacement and has good application potential.
[0079] As described above, the basic principles, main features, and advantages of the present invention have been well described. The above embodiments and specifications are merely descriptions of preferred embodiments of the present invention, and the present invention is not limited to the above embodiments. Various changes and improvements made to the technical solutions of the present invention by those skilled in the art without departing from the spirit and scope of the present invention should fall within the protection scope defined by the present invention.
Claims
1. A method for preparing a quantum fluorescent oil displacement agent, characterized in that, Includes the following steps: S1. Humic acid, phytic acid, urea and thiourea are dissolved in deionized water and hydrothermally reacted at 170~180℃ for 4~6h. Carbon quantum dot particles are obtained after post-treatment. S2. The carbon quantum dot particles obtained in S1 are dispersed in anhydrous ethanol and condensed with hydrolyzed and activated γ-aminopropyltriethoxysilane at pH 4-5 and 58-60℃ for 4-6 hours under the catalysis of dibutyltin dilaurate to obtain amino-modified carbon quantum dot materials. S3. The amino-modified carbon quantum dot material obtained in S2 is grafted with hexadecyltrimethylammonium bromide and betaine at pH 8-9 and 55-60℃ for 6-8 hours to obtain the quantum fluorescent oil displacement agent.
2. The preparation method according to claim 1, characterized in that, The mass ratio of humic acid, phytic acid, urea, and thiourea in step S1 is 1.5~2.5:0.1~0.5:0.7~1.0:0.05~0.
15.
3. The preparation method according to claim 1, characterized in that, The post-processing described in step S1 includes filtering sequentially using filter membranes with pore sizes of 0.8 μm and 0.45 μm.
4. The preparation method according to claim 3, characterized in that, The post-processing also includes: dialysis followed by freeze-drying using a combination of dialysis bags with molecular weight cutoffs of 4000 Da and 3000 Da.
5. The preparation method according to claim 1, characterized in that, The hydrothermal reaction in step S1 is carried out at a temperature of 180°C for 4 hours.
6. The preparation method according to claim 1, characterized in that, The condensation reaction in step S2 is carried out at a temperature of 60°C, a pH of 4.5, and a reaction time of 4 hours; the grafting reaction in step S3 is carried out at a temperature of 58°C, a pH of 8.5, and a reaction time of 6.5 hours.
7. The preparation method according to claim 2, characterized in that, The mass ratio of humic acid, phytic acid, urea, and thiourea is 2.5:0.2:1.0:0.
15.
8. The quantum fluorescent oil repellent prepared by any one of claims 1 to 7.
9. The application of the quantum fluorescent oil displacement agent according to claim 8 in oilfield development, characterized in that, The quantum fluorescent oil displacement agent is injected into the oil reservoir to improve the oil recovery rate, and the oil displacement process is monitored in real time by detecting its fluorescence signal.
10. The application according to claim 9, characterized in that, The quantum fluorescent oil displacement agent is injected into the formation at a concentration of 0.3wt% to 0.5wt%; the oil reservoir is a high-temperature and high-salinity oil reservoir with a temperature of 80 to 120°C and a salinity of 20,000 to 50,000 mg / L; the detection wavelength of the fluorescence signal is 500 to 600 nm.